THE EFFECT OF AUDITOR EXPERIENCE, AUDITOR WORKLOAD AND AUDITOR INCENTIVES ON PROFESSIONAL SKEPTICISM - Mulyadi, Roza; Ikhsan, Haerul; Yazid, Helmi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The aim of this research is to analyze the effect of auditor experience, auditor workload, and auditor incentives on professional skepticism. The respondents in this study are auditors working in Public Accounting Firms in the DKI Jakarta region. This research utilizes primary data and a questionnaire to obtain information from the respondents using purposive sampling method. The analysis method used is Statistical Program for Social Science (SPSS) version 25. The results of this research indicate that the variables of auditor experience, auditor workload, and auditor incentives have been proven to have a significant influence on professional skepticism.